Exercise‐conditioned plasma attenuates nuclear concentrations of DNA methyltransferase 3B in human peripheral blood mononuclear cells. Issue 12 (10th December 2015) - Horsburgh, Steven; Todryk, Stephen; Toms, Christopher; Moran, Colin N.; Ansley, Les
Abstract: DNA methylation is modifiable by acute and chronic exercise. DNA methyltransferases (DNMT) catalyze this process; however, there is a lack of literature concerning the specific mechanisms by which exercise‐induced modifications occur. Interleukin 6 (IL‐6) stimulation of various cell lines has been shown to augment DNMT expression and nuclear translocation, which suggests a possible pathway by which exercise is able to elicit changes in epigenetic enzymes. The present study sought to elucidate the response of the de novo methyltransferases DNMT3A and DNMT3B to circulatory factors found in plasma isolated from whole blood before and after 120‐min of treadmill running at an intensity of 60% of individual velocity at V ˙ O 2 max (v V ˙ O 2 max ) interspersed with 30‐sec sprints at 90% of v V ˙ O 2 max every 10‐min. Peripheral blood mononuclear cells (PBMCs) isolated from a resting participant were incubated with plasma isolated from exercising participants ( n  = 10) or recombinant IL‐6 (rIL‐6), followed by nuclear protein extraction and quantification of DNMT3A and DNMT3B concentrations. Nuclear concentrations of DNMT3B significantly decreased following the experimental protocol ( P  =   0.03), with no change observed in DNMT3A ( P  =   0.514).Various concentrations of rIL‐6 caused an elevation in both DNMT3A and DNMT3B nuclear concentration compared with the blank control. The conflicting results between exercising and rIL‐6 conditions suggests that IL‐6 does regulate DNMT nuclear transport, however, other plasma mediators may also exert significant influence on the nuclear concentrations of these enzymes. Abstract : The study sought to elucidate the underlying mechanisms by which exercise‐induced epigenetic modifications occur. Data show that DNMT3B, but not DNMT3A, is attenuated when PBMCs were cultured in the presence of exercise‐conditioned plasma. IL‐6 may be one of many plasma proteins involved in this complex process.